The Role of Geographical Factors in The Socio-Economic Development of Surkhandarya Region - Allanov KA; Choriev AK (Zien Journals, 2021)
This article discusses the geographical location, climate and factors that make up Surkhandarya, the southernmost region of the Republic of Uzbekistan. recommendations are illuminated
Keywords: Geographical location; subtropical climate; mineral resources; agriculture